Pengaruh Kebijakan Dividen, Kebijakan Hutang, Profitabilitas, Dan Harga Saham Terhadap Nilai Perusahaan - Hasrat Niatman Gulo; Enny Arita Arita (Jurnal Akuntansi Keuangan dan Bisnis, 2023)
This study aims to determine the effect of dividend policy, debt policy, profitability and stock prices on firm value. The population in this study were 44 mining companies. The sampling method used was the Purposive Sampling Method, so that 20 sample companies were obtained for 5 years of observation (2018-2022) with 20 observations. Research data obtained from the Indonesia Stock Exchange Website. The data analysis technique used was descriptive statistical analysis, regression analysis and hypothesis testing. The results of this study partially show that only Profitability and Stock Price have a significant effect on Firm Value, while Dividend Policy and Debt Policy have no significant effect on Firm Value. The results of the study simultaneously Dividend Policy, Debt Policy, Profitability and Stock Prices have a simultaneous effect on Firm Value.